FAKTOR-FAKTOR YANG MEMPENGARUHI KUNJUNGAN KE OBJEK WISATA KOMERSIAL”DI SUMATERA”BARAT - Miftahul Hasanah; Alpon Satrianto (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
The purpose of this studywas to determine the efect of income, gender, type of work, number of dependents, level of education to visit commercial tourist attractions in West Sumatra. This type of research is descriptive, where this study uses secondary data in the form of national socioeconomic survey data in 2017 and uses logistic regression methods. The results of this study indicate that income, type of work, number of dependents, level of education have a positive and significant effect on opportunities for tourist visits in West Sumatra, while gender, has a negative and significant effect on opportunities for tourist visits in West Sumatra.Keywords: tourist visits, income, gender type, type of work, number of dependents, education level.